2002
DOI: 10.4269/ajtmh.2002.66.590
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood diarrhea is associated with diminished cognitive function 4 to 7 years later in children in a northeast Brazilian shantytown.

Abstract: Abstract. Diarrhea is well recognized as a leading cause of childhood mortality and morbidity in developing countries; however, possible long-term cognitive deficits from heavy diarrhea burdens in early childhood remain poorly defined. To assess the potential long-term impact of early childhood diarrhea (in the first 2 years of life) on cognitive function in later childhood, we studied the cognitive function of a cohort of children in an urban Brazilian shantytown with a high incidence of early childhood diarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
161
3
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(180 citation statements)
references
References 11 publications
9
161
3
7
Order By: Relevance
“…Stunting, diarrheal disease, and parasitic infections caused mostly by malnutrition were also related to poor mental function [9]. In addition, a follow-up study that specifically addressed the possible long-term impact of early childhood diarrhea on cognitive function in later childhood suggested that childhood diarrhea was linked to deficits in cognitive abilities several years later [9,56].…”
Section: Relation Between Malnutrition Diarrhea and Cognitive Functionmentioning
confidence: 99%
“…Stunting, diarrheal disease, and parasitic infections caused mostly by malnutrition were also related to poor mental function [9]. In addition, a follow-up study that specifically addressed the possible long-term impact of early childhood diarrhea on cognitive function in later childhood suggested that childhood diarrhea was linked to deficits in cognitive abilities several years later [9,56].…”
Section: Relation Between Malnutrition Diarrhea and Cognitive Functionmentioning
confidence: 99%
“…1 Less severe cases of diarrhea, which are more likely to be treated in primary care clinics, are responsible for substantial morbidity. [2][3][4] To reduce the burden of rotavirus diarrhea, a growing number of nations are adding the rotavirus vaccine to their national immunization schedules. In clinical trials conducted primarily in the United States and Europe, the pentavalent rotavirus vaccine (RV5) reduced clinic visits for rotavirus diarrhea by 86%.…”
Section: Introductionmentioning
confidence: 99%
“…65,66 Despite surprisingly comparable growth curves in the first few months of life, the fall from the expected growth trajectory from 4 to 24 months of age in children living in impoverished areas of Asia, Africa, and Latin America has been remarkably consistent in decade-plus reviews as well as in current multisite studies. 3,67 The extent to which stunted growth is a reflection of intestinal parasitic or other infections or is predictive of impaired cognitive development, or that the latter may occur with an EE independent of stunted growth, has been and remains the topic of many studies ranging from work in Guatemala, 53 the Philippines, 51 Kenya, 63 Jamaica, 64,67 Peru, 68,69 and Brazil 70,71 to the current work by the Interactions of Malnutrition and Enteric Infections: Consequences for Child Health and Development consortium. 72 Evidence continues to mount that enteric infections and enteric or systemic inflammation in early childhood or prenatally can impair growth and development and perhaps even increase later life associations with obesity, metabolic syndrome or cardiovascular disease.…”
Section: The Impact Of Inflammation On Neurodevelopmentmentioning
confidence: 99%